Metode Fundraising Dana Zakat, Infak dan Sedekah pada Badan Amil Zakat Daerah (Bazda) Kabupaten Sukabumi - -, Niamulloh (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2013)
One of the important things in the institution of zakah is a method of fundraising, because raising money is the backbone of an organization. This research found that fundraising method of BAZDA Sukabumi to motivate donors through their programs in collecting zakah, donation, and charity from 2010 to 2011 undoubtedly increased the number of zakah, donation, and  charity to 20%,  which means that BAZDA Sukabumi has at least managed some potential zakat funds, donations, and charity in their own hometown. Keywords: fundraising, zakat, donations, and charity.